DIRECTIONS FOR IMPROVING THE QUALITY OF POSTGRADUATE EDUCATION OF PHYSICIANS - Н. Каспрук; С. Батрановська; С. Мельничук; Т. Унгурян; Т. Копчук; А. Петрюк (Неонатологія, хірургія та перинатальна медицина)
The pursuit and implementation of advanced information technologies in diagnostic and therapeutic processes are of paramount importance. It is essential to incorporate both national pedagogical experience and the educational practices of countries within the European educational space. Innovative teaching methods that facilitate a deeper understanding of theoretical concepts and support the acquisition of practical skills are fundamental to the evolving system of continuous professional development for medical practitioners. A key component in maintaining the quality of state-regulated postgraduate medical education, particularly in the context of ongoing healthcare reform in Ukraine, should be ensuring access to the full spectrum of educational formats utilized by international counterparts.